2014
DOI: 10.1371/journal.pone.0108824
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-Activated Potassium Current Modulates Ventricular Repolarization in Chronic Heart Failure

Abstract: The role of IKCa in cardiac repolarization remains controversial and varies across species. The relevance of the current as a therapeutic target is therefore undefined. We examined the cellular electrophysiologic effects of IKCa blockade in controls, chronic heart failure (HF) and HF with sustained atrial fibrillation. We used perforated patch action potential recordings to maintain intrinsic calcium cycling. The IKCa blocker (apamin 100 nM) was used to examine the role of the current in atrial and ventricular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
87
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(98 citation statements)
references
References 46 publications
6
87
0
5
Order By: Relevance
“…The heterogeneity might also contribute to the arrhythmogenecity in failing hearts. More recently, Bonilla et al and Ni et al confirmed these observations by showing that apamin significantly prolonged APD in failing human and canine ventricular cardiomyocytes, along with increased expression of SK channel protein in failing ventricles (Bonilla et al, 2014; Ni et al, 2013). The authors further demonstrated that there was a trend for more ventricular SK protein expression and greater APD prolongation in dogs with 4 months than with 1 month of HF.…”
Section: Differential Expression Of Sk Channels In Normal and Diseasementioning
confidence: 81%
See 2 more Smart Citations
“…The heterogeneity might also contribute to the arrhythmogenecity in failing hearts. More recently, Bonilla et al and Ni et al confirmed these observations by showing that apamin significantly prolonged APD in failing human and canine ventricular cardiomyocytes, along with increased expression of SK channel protein in failing ventricles (Bonilla et al, 2014; Ni et al, 2013). The authors further demonstrated that there was a trend for more ventricular SK protein expression and greater APD prolongation in dogs with 4 months than with 1 month of HF.…”
Section: Differential Expression Of Sk Channels In Normal and Diseasementioning
confidence: 81%
“…In neuronal cells, the SK channels account for the slow component of afterhyperpolarization, which regulates neuronal discharges. SK channels contribute to repolarization of action potential in atrial cardiomyocytes and diseased ventricular cells (Bonilla et al, 2014; Chang et al, 2013a; Chua et al, 2011; Lee et al, 2013; Xu et al, 2003). The activation of SK channels also plays important roles in the function of a range of other tissues, such as the endothelium, intestine and urinary bladder (Feher et al, 2014; Hougaard et al, 2009; Ro et al, 2001).…”
Section: The Discovery Of Sk Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…21 However, in HF, the contribution of ISK to repolarization during AP was demonstrated; and both an increase in expression levels and sensitivity to [Ca 2+ ] of SKCa channels in animal models and human HF have been established. 21,58, 59 Enhanced propensity to ventricular tachyarrhythmia is a major contributor to the death of patients with HF. Experiments using a rabbit model of tachypacing-induced cardiomyopathy demonstrated heterogeneous upregulation of SK channels, which can contribute to shortening of the APD and the development of ventricular fibrillation at fast rates.…”
Section: Skca and Ventricular Arrhythmia/hfmentioning
confidence: 99%
“…29 In line with our findings, single-cell electrophysiology studies of ventricular myocytes from a chronic canine model of HF demonstrated that SKCa inhibition effectively evokes AP instability. 59 Underscoring a protective role of SKCa channels in diseased hearts, blockade of SKCa channels in rabbit failing hearts was shown to enhance predisposition to Ca 2+ -dependent triggers exacerbating arrhythmic potential. 60 IR Injury/MI Recent findings from a rat model of acute MI indicate that SKCa channels in ventricular myocytes can be functionally recruited nearly instantaneously and subsequently evoke APD shortening in the MI zone within 10 min after ligation of the left anterior descending coronary artery.…”
Section: Skca and Ventricular Arrhythmia/hfmentioning
confidence: 99%